2017
DOI: 10.1093/molehr/gaw076
|View full text |Cite
|
Sign up to set email alerts
|

Application of microfluidic technologies to human assisted reproduction

Abstract: Microfluidics can be considered both a science and a technology. It is defined as the study of fluid behavior at a sub-microliter level and the investigation into its application to cell biology, chemistry, genetics, molecular biology and medicine. There are at least two characteristics of microfluidics, mechanical and biochemical, which can be influential in the field of mammalian gamete and preimplantation embryo biology. These microfluidic characteristics can assist in basic biological studies on sperm, ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 90 publications
0
61
0
6
Order By: Relevance
“…In the past decade, some microfluidic devices have been proposed for ART applications (27)(28)(29), including those that have been used to separate sperm (30). In one effort, a passive microfluidic system called microscale integrated sperm sorter (MISS) was proposed that could separate motile sperm from the rest of the sample (8).…”
Section: Significancementioning
confidence: 99%
“…In the past decade, some microfluidic devices have been proposed for ART applications (27)(28)(29), including those that have been used to separate sperm (30). In one effort, a passive microfluidic system called microscale integrated sperm sorter (MISS) was proposed that could separate motile sperm from the rest of the sample (8).…”
Section: Significancementioning
confidence: 99%
“…Similar to IVF, ICSI has been the choice of many patients with male infertility [53]. However, while the threat of oocyte lysis while inserting the needle into the oocyte still remains [54], the causes of oocyte degeneration have seldom been investigated [55]. One of the reasons for oocyte degeneration is technician error [56].…”
Section: Ivf With Microfluidicsmentioning
confidence: 99%
“…Raty et al demonstrated that mouse embryos cultured in microchannels had a greater number of blastocysts with a lower percentage of degenerated embryos than those with controlled microdrops [100]. However, the retrieval of the cultured embryos from the microchannels remains uncertain [54]. In 2004, Gu et al developed a microfluidic device with computer programming to regulate the fluid flow in the microchannel [101].…”
Section: Embryo Culture With Microfluidicsmentioning
confidence: 99%
“…The three-dimensional culture system can support the development of follicles by using biological materials to maintain cell-to-cell information exchange. In addition, mature oocytes can be obtained by using a three-dimensional culture system in the in vitro culture of anterior follicles of nonhuman primates [35], although no reports are available regarding the use of a three-dimensional culture system in the in vitro culture of immature human oocytes. A past study has used microreactors to form three-dimensional bioreactors to support the growth of different types of cells [36].…”
Section: Optimization Of Ivm Culture Environment and Processmentioning
confidence: 99%